Consistent effects of science and scientist characteristics on public trust across political regimes - Sukayna Younger-Khan; Nils B. Weidmann; Lisa Oswald (Humanities & Social Sciences Communications)
Abstract Recent years have seen an increased research interest in the determinants of public trust in science. While some argue that democracy should be the political regime most conducive to science, recent debates about salient scientific findings revealed considerable cracks in the public perception of science. We argue that existing cross-national work on trust in science is incomplete because it uses an aggregate concept of “science”. People in different political environments likely have different conceptions of what science is, which can have consequences for perceptions and trust. To remedy this shortcoming, we present results from a preregistered survey experiment in ten countries (N = 8441), which covers a broad spectrum of political regimes and tests how science and scientists’ characteristics influence public trust. We find that, against expectations, female scientists and scientists engaging in public activism are both perceived as more trustworthy. High-impact research is trusted more than low-impact research, and it does not matter whether a scientist is a co-national. Overall, our experiment reveals few differences across political regimes. Additional survey results show that respondents’ education and exposure to science have similar relationships with trust across autocratic and democratic countries. A striking difference we find is that while political orientation has little impact in autocratic countries, it is strongly related to trust across democracies as perceptions of science become increasingly politicized.